Description of Califorctenus (Cteninae, Ctenidae, Araneae), a new spider genus from Mexico - Jimenez, María Luisa; Berrian, James Edwin; Polotow, Daniele; Palacios-Cardiel, Carlos (Zootaxa, 2017)
Califorctenus gen. nov. (Araneae: Ctenidae) a new genus and a new species (Califorctenus cacachilensis sp. nov.) from the Baja California Peninsula in Mexico are described and illustrated. Califorctenus gen. nov. can be diagnosed by the morphology of the male palp, with embolus cylindrical and elongated, locking lobes of embolus positioned retrolaterally and the cup-shaped and elongated median apophysis.